Immediate implant in single rooted teeth - Study on primary stability and bone formation - Preetha Balaji; S M Balaji; Prashanti Ugandhar (Wolters Kluwer Medknow Publications, 2015)
Background: Dental implants (DI) are emerging as an alternative to dentures. Immediate placement of DI for esthetic concern has been always in demand. This is a retrospective analysis of the success rate of immediately placed DI in freshly extracted single-rooted tooth socket, by clinical, radiographical, soft and hard tissue changes in a follow-up period of 1 year. Materials and Methods: Retrospective analysis of all cases of immediate DI placed in the single rooted socket was performed. Cases were selected based on previously established inclusion and exclusion criteria. Age, gender, tooth, jaw, cause of impending tooth loss, tooth diameter along the cervical margin, the width of keratinized gingiva (WKG), and radiographic measures were performed for up to a year. Descriptive statistics and comparison of means were presented. P < 0.05 was taken as significant. Results: Of the 324 immediate DI placed in 207 patients during the study period, 61 fulfilled the criteria. There were 49.2% males 31.15% had dental caries, 61% involving maxilla. The mean age of patients was 34.82 ± 7.97 years. Mean extraction socket diameter was 4.6 ± 1.78 mm. From complete stability of DI, the WKG decreased from baseline to 3 months period and regained at 12-month follow-up. The difference was statistically significant (P = 0.01). The same trend was noticed in the distance of the mesial and distal papilla as measured in the probe (P = 0.075). Radiographical changes also reflected a similar trend. Discussion: The success of DI, in terms of clinical and radiographical parameters, in an immediate DI placed in a single rooted fresh extracted socket, gives adequate clinical results.